Pegunigalsidase alfa: a novel, pegylated recombinant alpha-galactosidase enzyme for the treatment of Fabry disease - Dominique P. Germain; Dominique P. Germain; Ales Linhart (Frontiers in Genetics, 2024)
Fabry disease, a rare X-linked genetic disorder, results from pathogenic variants in GLA, leading to deficient lysosomal α-galactosidase A enzyme activity and multi-organ manifestations. Since 2001, enzyme replacement therapy (ERT), using agalsidase alfa or agalsidase beta, has been the mainstay treatment, albeit with limitations such as rapid clearance and immunogenicity. Pegunigalsidase alfa, a novel PEGylated recombinant alpha-galactosidase, offers promise as an alternative. Produced in plant cells, pegunigalsidase alfa exhibits enhanced stability, prolonged half-life, and reduced immunogenicity due to pegylation. A phase 1/2 clinical trial demonstrated Gb3 clearance from renal capillary endothelial cells and its 48-month extension study revealed notable outcomes in renal function preservation. Three phase 3 clinical trials (BRIDGE, BRIGHT, and BALANCE) have shown favorable efficacy and safety profile, although caution is warranted in interpreting the results of BRIDGE and BRIGHT which lacked control groups. In BALANCE, the pivotal phase 3 trial comparing pegunigalsidase alfa with agalsidase beta, an intention-to-treat analysis of the eGFR decline over 2 years showed that the intergroup difference [95%confidence interval] in the median slope was −0.36 mL/min/1.73 m2/year [−2.44; 1.73]. The confidence interval had a lower limit above the prespecified value of −3 mL/min/1.73 m2/year and included zero. Despite challenges such as occasional hypersensitivity reactions and immune-complex-mediated glomerulonephritis, pegunigalsidase alfa approval by the European Medicines Agency and the Food and Drug Administration represents a significant addition to Fabry disease therapeutic landscape providing an option for patients in whom enzyme replacement therapy with current formulations is poorly tolerated or poorly effective.